Digital Marketing Impact on E-Commerce Business: Optimizing digital marketing strategies for online retailers (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Digital marketing strategy, digital media, digital marketing channels, digital marketing platforms,and the most crucially, digital marketing's enormous impact on the e-commerce sector. Increase in digitalmarketing, the difference between traditional and digital marketing, the impact of social media, the waybusinesses allocate their marketing budgets, the popularity of instant messaging platforms, the swayexerted by marketing channels, the globalization of e-commerce, and the role of digital marketing in egovernance.The true impact of digital marketing on customers' e-commerce spending must beevaluated. The best digital marketing communication strategies need to be evaluated. Thus, it isnecessary to examine the impact of digital marketing on purchases and determine the optimal use ofdigital marketing in various contexts. The study aims to shed new light on the topic in order to identifythe most impassive digital marketing techniques for online retailers.